Direct numerical simulation of a turbulent 90° bend pipe flow - Wang, Zhixin; Orlu, Ramis; Schlatter, Philipp; Chung, Yongmann M. (International Journal of Heat and Fluid Flow, 2018)
Direct numerical simulation (DNS) has been performed for a spatially developing 90° bend pipe flow to investigate the unsteady flow motions downstream of the bend. A recycling method is implemented to generate a fully-developed turbulent inflow condition. The Reynolds number of the pipe flow is ReD=5300 and the bend curvature is γ=0.4. A long straight pipe section (40D) is attached in the downstream of the bend to allow the flow to develop. Flow oscillations downstream of the bend are measured using several methods, and the corresponding oscillation frequencies are estimated. It is found that different characteristic frequencies are obtained from various flow measurements. The stagnation point movement and single-point velocity measurements may not be good measures to determine the swirl-switching frequency. The oscillations of the lateral pressure force on the pipe wall and half-sided mass flow rate are proposed to be a more unambiguous measure of the unsteady flow motions downstream of the bend.
CRIS-Team Scopus Importer:2023-03-21
Keywords: 90 degrees bend; Conditional averaging; Curved pipe; DNS; Swirl switching; Turbulent pipe flow